OR IAQ TASK FORCE (Tufts Archival Research Center, 2007)
Memo discussing strategy for Oregon Indoor Air Quality Task Force. Explains that the task force has an anti-smoking bent and that the labor representative on the task force is not an official representative of AFL-CIO. Discusses meeting with OR AFL-CIO President, where it was decided AFL-CIO would make a presentation to the task force. Plans for a strategy meeting with Donahue, BC&T, and other labor leaders.